Genome-wide meta-analysis identifies novel loci conferring risk of acne vulgaris - Teder-Laving, Maris; Kals, Mart; Reigo, Anu; Ehin, Riin; Objärtel, Telver; Vaht, Mariliis; Nikopensius, Tiit; Metspalu, Andres; Kingo, Külli (European journal of human genetics : EJHG, 2024)
Acne vulgaris is a common chronic skin disorder presenting with comedones, cystic structures forming within the distal hair follicle, and in most cases additionally with inflammatory skin lesions on the face and upper torso. We performed a genome-wide association study and meta-analysis of data from 34,422 individuals with acne and 364,991 controls from three independent European-ancestry cohorts. We replicated 19 previously implicated genome-wide significant risk loci and identified four novel loci [11q12.2 (FADS2), 12q21.1 (LGR5), 17q25.3 (FASN), and 22q12.1 (ZNRF3-KREMEN1)], bringing the total number of reported acne risk loci to 50. Our meta-analysis results explain 9.4% of the phenotypic variance of acne. A polygenic model of acne risk variants showed that individuals in the top 5% of the risk percentiles had a 1.62-fold (95% CI 1.47-1.78) increased acne risk relative to individuals with average risk (20-80% on the polygenic risk score distribution). Our findings highlight the Wnt and MAPK pathways as key factors in the genetic predisposition to acne vulgaris, together with the effects of genetic variation on the structure and maintenance of the hair follicle and pilosebaceous unit. Two novel loci, 11q12.2 and 17q25.3, contain genes encoding key enzymes involved in lipid biosynthesis pathways.